Harmonic cancellation of parallel-coupled bandpass filter with transmission zero realign method - Marimuthu, , Jayaseelan; Esa, , Mazlina (2005)
This paper presents the harmonic cancellation of a 3(rd) order Butterworth response parallel-coupled bandpass filter by introducing periodical grooves. ne cancellation was obtained by aligning the transmission zero of the Tight Coupling (TCg) coupler with the harmonic of the Weak Coupling (WCg) coupler. The alignment of transmission zero and harmonic was carried out by introducing square grooves periodically at the TCg and WGc couplers. Various numbers of grooves were introduced at the TCg and WCg couplers. By varying the number of grooves at the TCg coupler, the first transmission zero was obtained. Then similar method was used to align the harmonics of the WCg coupler with transmission zero of the TCg coupler. When three stage bandpass filter design with transmission zero of the TCg coupler is aligned with the harmonic of the WCg coupler, the overall the performance of filter improved in terms of suppression of the harmonics and cutoff frequencies.